Hesperidin Inhibits Inflammatory Response Induced by Aeromonas hydrophila Infection and Alters CD4+/CD8+ T Cell Ratio - Abdelaziz S. A. Abuelsaad; Gamal Allam; Adnan A. A. Al-Solumani (Hindawi Limited, 2014)
Background. Aeromonas hydrophila is an opportunistic bacterial pathogen that is associated with a number of human diseases. Hesperidin (HES) has been reported to exert antioxidant and anti-inflammatory activities. Objectives. The aim of this study was to investigate the potential effect of HES treatment on inflammatory response induced by A. hydrophila infection in murine. Methods. A. hydrophila-infected mice were treated with HES at 250 mg/kg b.wt./week for 4 consecutive weeks. Phagocytosis, reactive oxygen species production, CD4+/CD8+ T cell ratio, and CD14 expression on intestinal infiltrating monocytes were evaluated. The expression of E-selectin and intercellular adhesion molecule 1 on stimulated HUVECs and RAW macrophage was evaluated. Results. Percentage of CD4+ T cells in the intestinal tissues of infected treated mice was highly significantly increased; however, phagocytic index, ROS production, CD8+ T cells percentage, and CD14 expression on monocytes were significantly reduced. On the other hand, HES significantly inhibited A-LPS- and A-ECP-induced E-selectin and ICAM-1 expression on HUVECs and ICAM-1 expression on RAW macrophage. Conclusion. Present data indicated that HES has a potential role in the suppression of inflammatory response induced by A. hydrophila toxins through downmodulation of ROS production and CD14 and adhesion molecules expression, as well as increase of CD4+/CD8+ cell ratio.